Васюткино озеро: [рассказы] / Виктор Астафьев - Астафьев Виктор Петрович (Внеклассное чтение, 2021)
Экземпляры: ф.16 (20210622) / Инвентарный номер: 61045 / Цена: / Сис.шифр: 84(2Рос=411.2)6-4 / Авт.знак: А 91 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=411.2)6-44